Corporate Governance and Capital Structure Decisions: Evidence from Chinese Listed Companies - Vijayakumaran, S.; Vijayakumaran, R. (Journal of Asian Finance, Economics and Business, 2019)
This study examines the impact of corporate governance on capital structure decisions based on a large panel of Chinese listed firms. Using the system Generalized Method of Moments (GMM) estimator to control for unobserved heterogeneity, endogeneity, and persistency in capital structure decisions, we document that the ownership structure plays a significant role in determining leverage ratios. More specially, we find that managerial ownership has a positive and significant impact on firms’ leverage, consistent with the incentive alignment hypothesis. We also find that managerial ownership only affects the leverage decisions of private firms in the post-2005 split share reform period. State ownership negatively influence leverage decisions implying that SOEs may face fewer restrictions in equity issuance and may receive favourable treatments when applying for seasoned equity financing, thus use less debt. Furthermore, our results show that while foreign ownership negatively influences leverage decisions, legal person shareholding positively influences firms’ leverage decisions only for state controlled firms. We also find that the board structure variables (board size and the proportion of independent directors) do not influence firms’ capital structure decisions. Our findings suggest that recent ownership reforms have been successful in terms of providing incentive to managers through managerial shareholdings to take risky financial choices
Keywords: Ownership Structure; Corporate Governance; Leverage; Ownership Reform